JUSTIFICATION OF THE EVALUATION INDICATORS AND THE MECHANISM FOR IMPROVING THE EFFICIENCY OF THE MANAGEMENT SYSTEM OF THE MATERIAL RESOURCES SUPPLY OF THE OPERATIONAL TACTICAL GROUP OF TROOPS DURING THE CONDUCT OF A DEFENSE OPERATION - TELEHIN, Vadym (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In modern conditions, the general defense system should provide the possibility of centralized and decentralized management of material resources and be able to participate in the management of state defense. The effective functioning of the system of providing material resources is influenced by the timeliness and completeness of the financing of the needs of comprehensive provision of troops (forces). The reform of the Armed Forces of Ukraine envisages the introduction of electronic accounting systems for material and technical resources by NATO supply classes, bringing the volume of indestructible stockpiles of material resources in line with the real needs for these resources. In order to achieve strategic goals and fulfill the main tasks defined by the Strategic Defense Bulletin of Ukraine and the State Program for the Development of the Armed Forces of Ukraine, planned phased work is underway to implement reforms aimed at developing a single effective logistics system according to NATO standards, capable of providing effective support to all components of the defense forces , who, in the established order and under the conditions determined by the legislation of Ukraine, are involved in the implementation of the task of defense of the state as part of the defense forces. In addition, the experience of the Armed Forces of Ukraine and other components of the defense forces in the conditions of armed aggression by the Russian Federation indicates the need to create a system of providing material and technical means, works and services as a component of the system of providing the Armed Forces of Ukraine and other components of the defense forces during the joint performance of tasks with defense of the state. After all, the organization of the material support of the Armed Forces of Ukraine in practice showed that the existing system of rear, technical and medical support of the Armed Forces of Ukraine turned out to be limited in its ability to perform tasks during mobilization and operational deployment, as well as directly in the interests of the use of groups of troops (forces), therefore its functioning, both in peacetime and in a special period, needs drastic changes.